2015
DOI: 10.4049/jimmunol.1402326
|View full text |Cite
|
Sign up to set email alerts
|

Cornea-Infiltrating and Lymph Node Dendritic Cells Contribute to CD4+ T Cell Expansion after Herpes Simplex Virus-1 Ocular Infection

Abstract: Following herpes simplex virus type 1 (HSV-1) corneal infection, CD4+ T cells are expanded in the draining lymph nodes (DLN) and re-stimulated in the infected cornea to regulate the destructive inflammatory disease herpes stromal keratitis (HSK). The contribution of cornea resident, cornea infiltrating, and DLN resident dendritic cells (DC) to CD4+ T cell expansion in DLN and re-stimulation in corneas is unknown. Cornea resident and infiltrating DCs were selectively depleted by timed local (subconjunctival) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…It is also interesting that in the corneas of IFN-␣␤␥R Ϫ/Ϫ ¡WT mice at 9 dpi, virus was not cleared. Consistent with our data, the cornea relies on both the resident and early infiltrating immune cell response for a proper response to HSV-1 (48,49). Our data add that the IFN competence of infiltrating immune cells is necessary for efficient viral clearance in this normally avascular site.…”
Section: Discussionsupporting
confidence: 80%
“…It is also interesting that in the corneas of IFN-␣␤␥R Ϫ/Ϫ ¡WT mice at 9 dpi, virus was not cleared. Consistent with our data, the cornea relies on both the resident and early infiltrating immune cell response for a proper response to HSV-1 (48,49). Our data add that the IFN competence of infiltrating immune cells is necessary for efficient viral clearance in this normally avascular site.…”
Section: Discussionsupporting
confidence: 80%
“…The infiltrating DCs can pick up the viral antigens and migrate to the draining lymph nodes (DLNs) to prime virus specific T cells (19). Therefore, we next ascertained the number of CD11c+ cells in DLNs of HSV-1 infected B6 and NK1R −/− mice at early time-points post-infection.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that CD4 T cell priming in DLNs of HSV-1 infected mice could be due to the drainage of soluble viral antigens from infected corneas or the migration of cornea-infiltrating DCs loaded with viral antigens to the DLNs (19). Our results showed an increased number of cDCs in infected corneas and the DLNs of NK1R −/− than B6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…120 However, corneal epithelial cells are also able to express HLA class II molecules and present antigens directly to CD4+ T cells. 123 Histopathological examination of KC corneas reveals a moderate increase in the number of antigen-presenting cells compared to controls, but this increase is not as apparent as observed in inflamed corneas. 124 In …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 91%